1991
DOI: 10.1067/mva.1991.28565
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate clinical models and quantitative dipyridamole-thallium imaging to predict cardiac morbidity and death after vascular reconstruction

Abstract: Patients with peripheral vascular disease have a high prevalence of coronary artery disease and are at increased risk for cardiac morbidity and death after vascular reconstruction. The present study was undertaken to assess the value of 18 clinical parameters, of 7 clinical scoring systems, and of quantitative dipyridamole-thallium imaging for predicting the occurrence of postoperative myocardial infarction or cardiac death. Vascular surgery was performed in 125 patients. Thirteen postoperative cardiac events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Therefore, the sensitivity of stress-thallium scanning in detecting patients at risk for cardiac events after aortic reconstruction was 50%, the specificity was 51%, the positive predictive value was 22.9% and the negative predictive value was 77%. The frequency of serious cardiac events (MI, CHF, cardiac ischemia, arrhythmia leading to arrest) also was not different in patients having positive and negative studies (11.6% in patients with positive stress-thallium studies vs. 16.8% in patients with negative stress-thallium studies). The incidence of cardiac complications was low in patients with normal (no defects) stress-thallium imaging studies (nine events in seven patients), and only four serious complications (three episodes of cardiac ischemia without infarction and one episode ofCHF) occurred in three patients with normal studies (Table 3).…”
Section: Impact Of Preoperative Stress-thallium Scanningmentioning
confidence: 79%
“…Therefore, the sensitivity of stress-thallium scanning in detecting patients at risk for cardiac events after aortic reconstruction was 50%, the specificity was 51%, the positive predictive value was 22.9% and the negative predictive value was 77%. The frequency of serious cardiac events (MI, CHF, cardiac ischemia, arrhythmia leading to arrest) also was not different in patients having positive and negative studies (11.6% in patients with positive stress-thallium studies vs. 16.8% in patients with negative stress-thallium studies). The incidence of cardiac complications was low in patients with normal (no defects) stress-thallium imaging studies (nine events in seven patients), and only four serious complications (three episodes of cardiac ischemia without infarction and one episode ofCHF) occurred in three patients with normal studies (Table 3).…”
Section: Impact Of Preoperative Stress-thallium Scanningmentioning
confidence: 79%
“…The accuracy of DTS for evaluation of cardiac risk was first demonstrated by Boucher et al 21 in 54 patients indicated for vascular reconstuction and not eligible for ET and was confirmed by subsequent studies. 22 According to Eagle et al, 23 a combination of simplified clinical data and DTS optimizes preoperative evaluation of cardiac risk and reduces the need for coronary arteriography. The sensitivity of DTS is excellent (75% to 100% 21,[24][25][26] ) and its specificity is less good (55% to 72% 24-26 ) but can be enhanced by combination with other noninvasive methods.…”
Section: Discussionmentioning
confidence: 99%
“…Lette and colleagues found that the total point score of the Detsky modified risk index was the only feature of the clinical risk indices that correlated with the incidence of peri-operative cardiac morbidity [22]. In another study, it was found that Goldman and Detsky scores correlated with development of postoperative cardiac complications, but that most of the patients had been classified as low risk…”
Section: Clinical Evaluationmentioning
confidence: 99%